SCRIPTURE REVELATION AND CONSCIOUSNESS IN CHRISTIANITY AND HINDUISM - Harlod G. Coward, (Journal of Dharma, 1978)
The breadth of human experience is such that throughout the ages it has expressed itself through a wide range of structures of consciousness-from poetry to rational discourse to empirical endeavour. The phrase "structure of consciousness" here refers to an internal pattern in the psyche which orders and gives meaning to one's experience. In psychology today such "structures" are often technically referred to as "episternic styles" In each period of human history one of the~e structures or 1?a.tterns of consciousness (i.e. the poetic, the rational or the empirical) has tended to become dominant and establish itself as the philosophical presupposition or Weltanschauung of the age. As the philosopher Susanne Langer observes, this has the effect of culturally conditioning the general populace and even some of the educated who should know better into an uncritical acceptance of whatever way of thinking happens to be dominant at the time. This domination by one structure of consciousness, while not totally excluding the others, does effectively limit and shape t?e questions one may ask. Thus, concludes Langer, ~ach age: w~th its own way of seeing things, produces its own questions which III turn generate the particular academic enterprise of that era.